2011
DOI: 10.1111/j.1365-2834.2011.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact on the workload of the Ward Manager with the introduction of administrative assistants

Abstract: The widespread introduction of administrative assistance could increase ward productivity and provide support for clinical leaders. Continuing professional development for WMs needs to incorporate training about management responsibilities and how to best use administrative support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 6 publications
2
42
0
Order By: Relevance
“…, Locke et al . ). Furthermore, the expectations of subordinates and superiors were inconsistent with each other (Skytt et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…, Locke et al . ). Furthermore, the expectations of subordinates and superiors were inconsistent with each other (Skytt et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Locke et al . ). Additionally, clinical nursing activities include staff support, staff meetings, participation in reports, patient contact and managing the quality of care (e.g.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…40 Finally, nursing research in the administration / management field has only used the referential described by Yin, in single or multiple cases. This review identified studies focused on care management, nursing workload, 51 and nursing care planning. 54 In care management, a single case study involving nurses working in the hospital service sought to foster discussion, reflection and understanding of the importance of nurses' managerial practices for the quality of care and the assistance provided by health services.…”
Section: Discussionmentioning
confidence: 99%
“…48 The assessment of the nurse manager's workload was also carried out with a pilot project that introduced administrative assistants to health facilities in England. 51 The case study method has also been applied to evaluate care planning. In Australia this topic was explored focusing on advanced care planning and advanced home care guidelines for the elderly, focusing on the experiences of patients and families from three residences, and sought to plan the best care for the elderly in the final stage of life.…”
Section: Discussionmentioning
confidence: 99%